Spatially resolved infrared radiofluorescence: single-grain K-feldspar dating using CCD imaging - Mittelstraß, Dirk; Kreutzer, Sebastian (Geochronology, 2021)
The success of luminescence dating as a chronological tool in Quaternary science builds upon innovative methodological approaches, providing new insights into past landscapes. Infrared radiofluorescence (IR-RF) on K-feldspar is such an innovative method that was already introduced two decades ago. IR-RF promises considerable extended temporal range and a simple measurement protocol, with more dating applications being published recently. To date, all applications have used multi-grain measurements. Herein, we take the next step by enabling IR-RF measurements on a single grain level. Our contribution introduces spatially resolved infrared radiofluorescence (SR IR-RF) on K-feldspars and intends to make SR IR-RF broadly accessible as a geochronological tool. In the first part of the article, we detail equipment, CCD camera settings and software needed to perform and analyse SR IR-RF measurements. We use a newly developed ImageJ macro to process the image data, identify IR-RF emitting grains and obtain single-grain IR-RF signal curves. For subsequent analysis, we apply the statistical programming environment R and the package Luminescence. In the second part of the article, we test SR IR-RF on two K-feldspar samples. One sample was irradiated artificially; the other sample received a natural dose. The artificially irradiated sample renders results indistinguishable from conventional IR-RF measurements with the photomultiplier tube. The natural sample seems to overestimate the expected dose by ca. 50 % on average. However, it also shows a lower dose component, resulting in ages consistent with the same sample's quartz fraction. Our experiments also revealed an unstable signal background due to our cameras' degenerated cooling system. Besides this technical issue specific to the system we used, SR IR-RF is ready for application. Our contribution provides guidance and software tools for methodological and applied luminescence (dating) studies on single-grain feldspars using radiofluorescence.
Gesehen am 31.03.2025